Maximizing nutrition in key food value chains of Mongolia under climate change - Dagys, Kadirbyek; Bakyei, Agipar; Tsolmon, Soninkhishig; Ringler, Claudia; Bellisario, Kristen; Fanzo, Jessica (Elsevier, 2023)
Mongolia’s projected warming is far above the global average and could exceed 5 °C by the end of the century. The reliance on pastoral livestock and rainfed agriculture along with its fragile ecosystems put Mongolia’s economy at risk of adverse climate change impacts, particularly from climate extreme events. Eighty percent of Mongolia’s agricultural sector is concentrated in animal husbandry with around one third of the population relying on this livelihood. Beyond livestock, food production is concentrated in few crops: wheat; potatoes; and three vegetables (cabbage, carrot, and turnip). Climate change does not only affect food production but can exacerbate malnutrition by removing food and nutrients in all stages of the food value chain. To identify perceived effects of climate change and measures to reduce climate change impacts in Mongolia's’s key food value chains, we implemented focus group discussions with 214 livestock and vegetable producers, traders, and food consumers. We also conducted 30 key informant interviews at the soum, provincial, and national levels across four agroecosystems in three provinces. Based on this community engagement analysis, we identify interventions that the government and private sector, including herders and farmers, should undertake to increase the food security and nutrition of the country’s prioritized food value chains under climate change.